Curcumin and Novel Synthetic Analogs in Cell-Based Studies of Alzheimer’s Disease - Gagliardi, Stella; Franco, Valentina; Sorrentino, Stefano; Zucca, Susanna; Pandini, Cecilia; Rota, Paola; Bernuzzi, Stefano; Costa, Alfredo; Sinforiani, Elena; Pansarasa, Orietta; Cashman, John R.; Cereda, Cristina (Frontiers in Pharmacology, 2018)
Alzheimer’s disease (AD) is a chronic neurodegenerative disorder that is associated with the most common type of dementia and is characterized by the presence of deposits of the protein fragment amyloid beta (Aβ) in the brain. The natural product mixture of curcuminoids that improves certain defects in innate immune cells of AD patients may selectively enhance Aβ phagocytosis by alteration of gene transcription. In this work, we evaluated the protective effects of curcuminoids in cells from AD patients by investigating the effect on NF-κB and BACE1 signaling pathways. These results were compared to the gene expression profile of the clearance of Aβ. The minor curcumin constituent, bisdemethoxycurcumin (BDC) showed the most potent protective action to decrease levels of NF-κB and BACE1, decrease the inflammatory cascade and diminish Aβ aggregates in cells from AD patients. Moreover, mannosyl-glycoprotein 4-beta-N-acetylglucosaminyltransferase (MGAT3) and vitamin D receptor (VDR) gene mRNAs were up-regulated in peripheral blood mononuclear cells from AD patients treated with BDC. BDC treatment impacts both gene expression including Mannosyl (Beta-1,4-)-Glycoprotein Beta-1,4-N-Acetylglucosaminyltransferase, Vitamin D and Toll like receptor mRNA and Aβ phagocytosis. The observation of down-regulation of BACE1 and NF-κB following administration of BDC to cells from AD patients as a model system may have utility in the treatment of asymptomatic AD patients.